Monetary Policy of Reserve Bank of India: Role of Bank Lending - Sircar, Subhalakshmi; Goel, Sandeep (Arthshastra Indian Journal of Economics & Research, 2015)
The global meltdown of 2008 challenged the sanctity of the monetary policy of the Central banks worldwide. However, it is a fact that the monetary policy is a vital tool in the hands of the Central bank of any country for stabilizing the economy. India is no exception to it. Reserve Bank of India (RBI), the central bank of the country, also uses this tool for rejuvenating the economy. This is where monetary tools like repo rate, reverse repo rate, and cash reserve ratio emerge. The present paper reviewed the current state of the monetary policy of RBI with respect to its focus on the objective of price stability and its impact on the Indian economy through the credit channel of monetary transmission mechanism.